MANAJEMEN PESERTA DIDIK : PPDB, LAYANAN BK, PEMBINAAN KARAKTER, DAN KOLABORASI GURU-ORANGTUA DI UPT SDN 24 KALIBONE KABUPATEN PANGKAJENE DAN KEPULAUAN - Sitti Aisyiah; Suardi; Idawati (STKIP Subang, 2025)
This research report aims to evaluate the effectiveness of student management at UPT SDN 24 Kalibone, which includes the New Student Admissions (PPDB) policy, Guidance and Counseling (BK) services, psychopedagogic-based character building, school security systems, and collaboration with parents. Student management at the elementary level has a crucial role not only in administrative aspects, but also as an instrument for developing the potential and character formation of children aged 7-12 years. Data collection methods were carried out through field observations, in-depth interviews with the Principal and Teachers, and the distribution of questionnaires via Google Form to teachers and parents of students. Data analysis was carried out descriptively and evaluatively to capture the gap between Educational management theory and practice in the field. The Evaluation Results show that; The implementation of PPDB has been running objectively and transparently through the zoning system, but support for Inclusive Education is still hampered by the availability of Special Guidance Teachers (GPK). Services at the school are still reactive and are carried out concurrently by class teachers due to the lack of specialist staff, so that the psychopedagogical approach has not been formally integrated into learning. Character building has been successful at the routine habituation stage (such as the 5S culture), but still requires improvement in risk mitigation at home time and monitoring of digital bullying. Collaboration with parents remains transactional and administrative and has not yet optimally synchronized moral standards between home and school. This report recommends the need for a transformation of school policies focused on strengthening inclusive services, implementing a reward-based positive discipline system, and innovations to build synergy between moral and holistic education.